Cytotoxic activity of methanolic extract of Artocarpus heterophyllus against A549, Hela and MCF-7 cell lines - Rajesh M.Patel, Sahil K. Patel (Journal of Applied Pharmaceutical Science)
Research is focusing on the search for new types of natural chemotherapeutic agents derived from plants which are proving to be excellent sources of new compounds. The present research article was aimed to study the cytotoxic activity of methanolic extracts of Artocarpus heterophyllus plant by various in vitro cytotoxic assays like MTT and SRB against different cell lines like HEK293, A549, HeLa and MCF-7. The IC50 values of methanolic extract of Artocarpus heterophyllus were found 35.26 µgm/ml and 35.27 µgm/ml against A549 cell line by MTT and SRB assay methods respectively whereas this extract was found to be non toxic to normal cells (HEK293), proved that the methanolic extract exhibited significant anti cancer potential with no toxicity on normal cell line. The methanolic extract had no activity against Hela and MCF-7 cell line.
Keywords: Cytotoxicity, SRB, MTT, Extraction.